IDX Regulation on Audit Delay (Kep-00027/BEI/03-2020): Evidence Before, During, and After the COVID-19 - Negara, Hari Kusuma Satria; Purnamasari, Diah Indri; Hastuti, Sri; Kasih, Puji Handayani; Winata, Isnu Angga (RSF Conference Series: Business, Management and Social Sciences, 2025)
Audits play a crucial role in ensuring the reliability of financial statements for stakeholders. However, audit delay may undermine information quality, reduce market confidence, and disrupt decision-making. To address these challenges, the Indonesia Stock Exchange (IDX) issued Regulation Kep-00027/BEI/03-2020, which relaxed reporting deadlines. Nevertheless, limited studies have examined the effectiveness of this regulation across the periods before, during, and after the COVID-19 pandemic. This study aims to analyze the impact of IDX regulation on audit delay by considering auditee characteristics, auditor characteristics, and external factors, with audit tenure as a moderating variable and COVID-19 as a control variable. However, the study focuses specifically on manufacturing companies listed on the IDX during the period from 2016 to 2024. The research sample is drawn from this population, consisting of manufacturing companies listed on the IDX between 2016 and 2024. This research employs regression analysis on 135 observations, divided into three periods: before (2016-2019), during (2020-2022), and after (2023-2024). The findings reveal that the relaxation policy helped reduce audit delay during the pandemic, although its effectiveness varied depending on firm size, profitability, ownership, and operational complexity. Audit tenure demonstrated a dual role: facilitating faster audits for complex firms due to the accumulated knowledge of the auditor, yet potentially compromising independence when the relationship extended excessively.